Meningkatkan Pengendalian Emosi Tunalaras Melalui Film “Jalan Pulang” Di BRSBKL Yogyakarta - Alaudin Ghaly Argyanto; Daratul Baidah; Putri arum Sari; Gudang Budiman; Muhammad Syahrul Fadilah; Fiza Nafisatun Najah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This research aims to improve emotional control of the mentally retarded through showing the film "Walk Home" at the Bina Karya and Laras Social Rehabilitation Center (BRSBKL). Disabled individuals are individuals who experience emotional and behavioral disorders, so they require a special approach to help them manage their emotions better. Movie watching therapy was chosen because of its interactive and fun nature, as well as its ability to convey moral messages, improve mood, and stimulate self-reflection. The research method used is through film screening which consists of three main stages, namely the planning, implementation, and evaluation and reflection stages. The research results show that watching films regularly can have a positive impact on character formation and managing the emotions of inmates.